PEDAGOGI USUL AL FIQH BERBASIS PENDIDIKAN PERDAMAIAN DI ERA MULTIKULTURAL - Rusli, Rusli (ULUL ALBAB Jurnal Studi Islam, 2011)
This article discusses the role of usul al fiqh in constructing humanist values and principles to build ‘peace education’ in the current multicultural era. Usul al fiqh is considered as the source of value and change, and has played a significant role to start reforms in legal and social institutions because of the pressures of context and religious integrity. The values contained in the sources of Islamic law, such as al Quran, Sunnah, ijma', qiyas, istislah, istihsan, sadd al dhara'i, and also maqasid al shari'ah, are translated into the community and are wholly implemented in the educational institutions. These values are transmitted to the learners through methods such as dialogue, cooperation, problem solving and the democratic limit creation. In transferring knowledge and values, an educator must be grounded on two important approaches: first, encouraging respect to the diversity based on the concept that education as a mirror, window, and conversation; second, doing class activity which is more cooperative based on the principle of justice and equality.